Technikerwerb im Badminton - Diskrepanzen im Lernerfolg zwischen Bewegungsablauf und Bewegungsresultat - Gawin, W.; Jaitner, T. (Messplätze, Messplatztraining, motorisches Lernen: ausgewählte Beiträge; 5. gemeinsames Symposium der dvs-Sektionen Biomechanik, Sportmotorik und Trainingswissenschaft; Universität Leipzig, Sportwissenschaftliche Fakultät, 19. bis 21. September 2002, 2003)
A learning experiment was performed to investigate the coherence between performance and result of movement techniques. 20 students participated in pre- and posttest and learned in-between the backhand overhand stroke in Badminton during a three-week learning-period. The results showed that some subjects revealed a change in performance (as rated by experts) above average concerning the result (measured as distance from a given aim) of the technique. While three subjects showed a remarkable backstep in accurateness combined with an increase in performance, four other subjects hardly improved performance although accurateness was rated remarkably higher. Therefore remarkable differences in one distinctive variable of the qualitative evaluation of physical skills may not cause equal results in effect related features. Further the problem of subjectiveness of experts is discussed.